Lary: Inovasi Media Pembelajaran Sejarah Berbasis Pahlawan Lokal Lampung Sebagai Upaya Pengintegrasian Pendidikan Karakter bagi Generasi Emas - Sumargono, Sumargono; Aswandi, Vany; Kusuma, Imroah Laina Retno Mukti (Keraton: Journal of History Education and Culture, 2022)
The use of history learning media is one of the factors that support the course of the learning process, for this reason, it is necessary to apply appropriate learning media in the learning process. Local history provides awareness that facilities are needed on the delivery of values that can be the main breakthrough of the student's character cultivation plan. This research discusses the development of history learning media through the application of local history with material on local heroes in Lampung as an effort to integrate character education. This research uses research and development (R&D) methods adapted from the 4-D development research model. Data collection techniques used in this study include interviews, literature studies, observations and questionnaires. Learning media developed feasibility are used as learning media based on due diligence by material experts getting a percentage of 94% value and media experts getting a percentage value of 92%, overall stating that android-based learning media to introduce students to the historical relics of the pre-script period in Lampung is worthy of being used as a historical learning media. The results of the SPSS 17.0 analysis obtained significantly at 0.000 < 0.05 this shows that there is a significant difference between class XI IPS 1 as an experimental class and class XI IPS 2 as a control class after testing. The difference in the results of the average attitude scale test of the experimental class of 75,3 and the control class of 68,75, this shows that the historical learning media through the application developed is effective in instilling the values of character education for students.